(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2022)
The situation caused by the global pandemic emerging from the COVID19 event has led the University to rethink organizational models and forms of operation in its essential missions in the present. Among them, the university extension was questioned in many aspects and above all in those that highlight its interrelation with the territories from the Inter game of the actors and the forms of intervention and focused linkage. In this work we intend to account for nodal aspects of this situation from initial questions, which question us as committed actors from the hand of a reflective view of practices and the consequent production of knowledge that has been taking place. In this way we will address the questions, and the literature produced in order to present a narrative made up of some sentimental developments that from the extension with social commitment at the National University of San Luis that we have been putting in tension.